FOCUS ON MAGNESIUM BASED DRUGS - I. I. Esenova (Рациональная фармакотерапия в кардиологии)
Magnesium deficiency in the organism is one of the most common human deficiency states. The prevalence of magnesium deficiency is about 15%, and suboptimal magnesium level is observed more than in 30% of people in the general population. Clinical signs of hypomagnesaemia are observed in 40% of patients in general care hospitals, in 70% of patients - in intensive care units, and magnesium deficiency occurs in 90% of patients with acute coronary syndrome. Magnesium metabolic disorders in the organism accelerate significantly development of complications of coronary heart disease, hypertension, type 2 diabetes, asthma and a number of neurological and psychiatric diseases. The value of this macro in the body is well studied, and its daily need is identified depending on age and sex. It is known that magnesium intake with the food does not cover an organism need. It is a rationale for preventive and therapeutic use of magnesium based drugs in various diseases. Organic salts of magnesium are recommended for these purposes. Magnesium metabolic disorders, approaches to pharmacotherapeutic correction of magnesium deficiency, advantages of magnesium salts of orotic acid are reviewed.